Morphological and cultural variation in different oilseed Brassica isolates of Alternaria brassicae from different geographical regions of India - GOYAL, P; CHAHAR, M; MATHUR, A P; KUMAR, A; CHATTOPADHYAY, C (The Indian Journal of Agricultural Sciences, 2011)
Variation in morphology and cultural characteristics among 13 representative Indian geographical isolates from 219 collections of Alternaria brassicae, the causal agent of Alternaria blight of rapeseed-mustard, was studied. All the isolates showed high level of variability in vitro in respect of conidia length, width, beak length and number of septa. Conidia of Nazirhat isolate (SS 04) were smallest in size with lowest number of septa. Substantial variation was found in mycelial growth, sporulation among these isolates in different nutrient media and artificial environmental condition, viz temperature, relative humidity, light, hydrogen ion concentration. Different temperature ranges (25–30 Degree Celcius; 15–35 Degree Celcius) were found optimum for different isolates for mycelial growth and sporulation, respectively. All the thirteen isolates grew best at 100% relative humidity. However, they sporulated the most at different % relative humidity (40–100%). This reflected the adaptation of the respective isolates to the ambient conditions in the different cropping areas, where the disease occurs in varied proportions in different years, which may have also induced the available cultural variability. All the isolates did not grow and sporulate abundantly on the same nutrient medium. However, on an average Asthana and Hawker’s medium was good for all the cultures. Variation in optimum pH and light condition for mycelial growth, sporulation was also observed. Cluster analysis for data on cultural variability among thirteen A. brassicae isolates found a close relationship among isolates from Uttar Pradesh, Uttaranchal and Haryana but was distantly related to others.